A Decade of Research Design Studies: A Bibliometric Analysis (2012-2022) - Deda, Yohanis Ndapa; Disnawati, Hermina (Bulletin of Pedagogical Research, 2024)
Research design is a didactic-oriented research method, predicting student responses before learning and paying attention to student conditions during and at the end of learning. However, comprehensive studies have yet to show trends in design research worldwide. This study investigates design research trends through bibliometric study of widespread and open-access databases, namely the Google Scholar and Scopus databases, from 2012 to 2022. We reviewed 997 documents from Google Scholar and 94 from the Scopus database on Harzing's Publish or Perish (PoP) 8.7.4245.8399 version on March 10, 2023. The descriptive analysis approach was employed to analyze the data; data from PoP was processed using Microsoft Excel and VoSViewer. The vizualitation show that there are four significant clusters related to design research are the learning process, local instructional theory, realistic mathematics education, and didactical design research. The findings can help scholars identify design research trends and guide future investigations because in the last three years (2020-2022), there aren’t recent research related to design research. Future research should compare Google Scholar, Scopus, other sources to investigate more years, and deepen meta-analysis on design research. Keywords: Bibliometric Analysis, Design Research, Scopus, Google Scholar